2018
DOI: 10.1080/13625187.2018.1506101
|View full text |Cite
|
Sign up to set email alerts
|

Phase II dose-finding study on ovulation inhibition and cycle control associated with the use of contraceptive vaginal rings containing 17β-estradiol and the progestagens etonogestrel or nomegestrol acetate compared to NuvaRing

Abstract: Contraceptive rings releasing 300 µg E2 and 75-125 µg/day of ENG or 500-900 µg/day of NOMAC provided adequate ovulation inhibition and cycle control and are generally well-tolerated. While non-inferiority to NuvaRing was not met, among the investigational rings, the ENG-E2 125/300 ring provided the best cycle control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Model simulations confirm that low and high doses of exogenous progestin reduce the LH surge to non-ovulatory levels as suggested by clinical data [16,17] for progestin treatments. Also low and high doses of exogenous estrogen reduce the LH surge to non-ovulatory levels.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Model simulations confirm that low and high doses of exogenous progestin reduce the LH surge to non-ovulatory levels as suggested by clinical data [16,17] for progestin treatments. Also low and high doses of exogenous estrogen reduce the LH surge to non-ovulatory levels.…”
Section: Introductionsupporting
confidence: 54%
“…Ovulation is broken into two stages and the luteal phase into four stages. Equations calculating ovarian hormones, assumed proportional to masses in different stages, are in Eqs 14- (17). In Eqs (14) and 15exogenous doses of estrogen (e dose ) and progestin (p dose ) are added, respectively.…”
Section: Plos Computational Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…With the second combined hormonal pill containing E2 and nomegestrol acetate in a 24/4 regimen, women experienced a decrease in unscheduled bleeding over time and increase in amenorrhea with continued use [22]. Bleeding patterns with investigational CVRs containing E2 and various doses of nomegestrol or etonogestrel showed that unscheduled bleeding decreases over time with all rings; however, bleeding predictability may not compare with ethinyl estradiol-based contraceptives [23,24]. In this study, we evaluated CVRs containing three doses of E2 combined with a progestin dose that effectively suppresses follicular development and endogenous ovarian estrogen synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have shown that E4 does not induce hepatic synthesis of SHBG and does not affect the activity of cytochrome P450, which inhibits ovulation in a dose-dependent manner and which acts as estrogen in the vagina, uterus and bone [55]. These premises have supported phase II studies with the use of E4 as an OC in combination with DRSP or LNG, which have shown efficacy in inhibiting ovulation, with a low metabolic impact on the synthesis of liver proteins [56][57][58]; phase III studies show the efficacy and safety of the OC containing 15 mg of E4+3 mg of DRSP [59].…”
Section: Prospects For the Future Of Oc With Natural Estrogenmentioning
confidence: 93%